SAE Technical Paper Series 2004
DOI: 10.4271/2004-01-1477
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Cell APU for Silent Watch and Mild Electrification of a Medium Tactical Truck

Abstract: This paper investigates the opportunities for improving truck fuel economy through the use of a Fuel Cell Auxiliary Power Unit (FC APU) for silent watch, as well as for powering electrified engine accessories during driving. The particular vehicle selected as the platform for this study is a prototype of the Family of Medium Tactical Vehicles (FMTV) capable of carrying a 5 ton payload. Peak stand-by power requirements for onboard power are determined from the projected future digitized battlefield vehicle requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Based on this correlation, the predicted fuel economy from GT-Drive simulation is quite acceptable for the baseline vehicle. primary, and 30% cross-country roads) [14].…”
Section: Fuel Economy Correlation Between Simulation and Experimentalmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this correlation, the predicted fuel economy from GT-Drive simulation is quite acceptable for the baseline vehicle. primary, and 30% cross-country roads) [14].…”
Section: Fuel Economy Correlation Between Simulation and Experimentalmentioning
confidence: 99%
“…This project adopts the driving cycle of [14,18] which is created from portions of the Munson Road course at the Aberdeen Proving Ground and a modified U.S. Environmental Protection Agency (EPA) driving schedule [19]. Shown in Figure 5, a typical mission schedule of the LMTV includes the beginning segments of varying vehicle speed over flat terrain with frequent accelerations and decelerations (the primary and secondary roads), and then a segment with varying grades at a constant vehicle speed (cross-country road).…”
Section: Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the VESIM model used in this work is given in [2,8]. It includes the embedded hydraulic system consisting of a pump/motor, a transfer case, a reservoir, and an accumulator [2].…”
Section: Optimal Hydraulic-hybrid Powertrain Design For a Dual-use Mementioning
confidence: 99%
“…To eliminate the need for excessive near-idle engine operation and overcome the energy density and capacity disadvantages of batteries, while fully exploiting the benefits of the hybrid-hydraulic configurations, fuel cells (FC) are considered as auxiliary power units (APUs) enabling electrification of powertrain components [3][4][5][6][7]. A recent simulation-based analysis demonstrated that using a fuel cell APU can improve fuel economy up to 10% while driving and almost six times while at standstill, during the silent watch (relative to using a diesel engine only) [8]. The benefits of electrifying the accessories and powering them with the FC APU during driving are over-and-above the improvements resulting from hybridization.…”
Section: Introductionmentioning
confidence: 99%